Synthesis and Biological Evaluation of Novel Piperazine Containing Hydrazone Derivatives - Betül Kaya; Yusuf Özkay; Halide Edip Temel; Zafer Asım Kaplancıklı (Journal of Chemistry)
Some hydrazone derivatives were synthesized and their potential anticholinesterase activities were examined. A series of eleven new compounds of N′-(2,4-disubstitutedbenzylidene)-2-(4-(4-nitrophenyl)piperazin-1-yl)acetohydrazide derivatives were obtained via reaction of 2-[4-(4-nitrophenyl)piperazin-1-yl]acetohydrazide with aromatic aldehydes. The chemical structures of the compounds were enlightened by FT-IR, 1H-NMR, 13C-NMR, and HRMS (ESI) spectral data. The inhibition potency of the compounds 3a–k against AChE and BuChE was measured and evaluated using a modification of Ellman’s spectrophotometric method. Among the tested compounds, compound 3c was assigned to be the most active derivative. Galantamine was used as a standard drug.